PENGARUH NILAI BELANJA HEDONIS DAN UTILITARIAN TERHADAP LOYALITAS DESTINASI WISATA DENGAN KEPUASAN BELANJA SECARA KESELURUHAN SEBAGAI VARIABEL MEDIASI PADA DESTINASI WISATA KOTA SABANG - Irbahani Sarmina, Syarifah Evi Zuhra (Departemen Manajemen, 2016)
The aims of this study are to investigate the effect of hedonic shopping value and utilitarian shopping value on destination loyalty with overall shopping satisfaction as mediation variable. Tourist of travel destination in Sabang city is taken as sample in this study. The method of this study’s non-probability technique. Hierarchical Linear Modeling methods of analysis are used to determine influence of the variables involved. The result of this study indicates that hedonis shopping value have positive effect on destination loyalty, utilitarian shopping value have positive effect on destination loyalty, hedonic shopping value and utilitarian shopping value have positive effect on destination loyalty with overall shopping satisfaction as mediation variable. In addition obtained results that overall shopping satisfaction has partial mediated the effect of hedonic shopping value to destination loyalty and overall shopping satisfaction has partial mediated the effect of utilitarian shopping value to destination loyalty.Keyword: Hedonic Shopping Value, Utilitarian Shopping Value,Overall Shopping Satisfaction, Destination Loyalty